The Effect Of Forensic Audit On The Fraud Prevention With Accountability As An Intervening Variable In Village Government In Langkat Regency - Abdul Habib Sitompul; Rahima Br Purba (Journal of Research in Social Science and Humanities, 2025)
This study aims to analyze the effect of forensic audits on preventing village fund corruption with accountability as an intervening variable in village governments in Langkat Regency. This study uses a quantitative approach with a survey method to 150 village government officials. SEM PLS-based path analysis is used to test the direct and indirect relationships between the research variables. The results show that forensic audits have a positive and significant effect on preventing village fund corruption, both directly and through the accountability variable as a mediator. This finding confirms that the effectiveness of forensic audits will be more optimal if followed by increased accountability of village officials in every stage of financial management. This study provides implications that local governments need to strengthen forensic audit capacity and encourage a culture of accountability to minimize the risk of village fund corruption.